An Algorithm-based Approach to Map the Players’ Network for Photovoltaic Energy Businesses - Schaefer, Jones Luís; Siluk, Julio Cezar Mairesse (International Journal of Sustainable Energy Planning and Management, 2021)
Due to economic, social, and environmental factors that influence businesses related to renewable energy sources, such as photovoltaic energy (PV), several players are acting on these business models, forming a complex network of interrelations. In this sense, this paper aims to identify the players involved in PV businesses, mapping the main relations between the players, and discussing these interactions in the context of PV businesses. A systematic review (SR) based on the Preferred Reporting Items for Systematic Reviews and a Meta-Analyses (PRISMA) statement was used to identify who the players were and to group them into clusters. The Apriori algorithm was used to build a players’ network and a clusters’ network, enabling a detailed discussion of these relationships. 35 players were identified, being grouped into 7 clusters, which can be related to the PV’s businesses. 20 players achieved relevance through Apriori rules, appearing in the players’ network. With the players’ network related to the PV businesses, business models can be defined or improved, exploring the conditioning, and limiting factors to improve business processes.